The problem of time in gravitation and cosmology - Chataignier, Leonardo (Cadernos de Astronomia, 2025)
IIn this outreach review, we discuss key concepts of quantum theory and their application to the construction of a quantum theory of gravitation and cosmology. Of special significance is the problem of time: how can we understand the evolution of a quantum Universe if there is no classical variable that represents an absolute time?
Keywords: quantum gravity; quantum cosmology; problem of time